Réponses

2013-05-04T16:59:30+02:00

a)

x² - 4 = 0

(x - 2)(x + 2) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

donc

x - 2 = 0

x - 2 + 2 = 0 + 2

x = 2

 

OU

x + 2 = 0

x + 2 - 2 = 0 - 2

x = -2

 

b)

x(x - 3) + 2(x - 3) = 0

(x - 3)(x + 2) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

 

donc

x - 3 = 0

x - 3 + 3 = 0 + 3

x = 3

 

OU 

x + 2 = 0

x + 2 - 2 = 0 - 2

x = -2

 

c)

x² + 5x = 0

x(x + 5) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

donc

x = 0  

 

OU x + 5 = 0

x + 5 - 5 = 0 - 5

x = - 5  

 

d) 4x² - 7x = 0

x(4x - 7) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

donc

x = 0  

 

OU

4x + 7 = 0

4x + 7 - 7 = 0 - 7

4x / 4 = -7/4

x = -7/4